2016
DOI: 10.1590/s0102-865020160020000007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of allopurinol as a protective factor in post ischemia and reperfusion inflammation in Wistar rats

Abstract: PURPOSE:To investigate the potential protective effect of allopurinol on reperfusion injury by determining the inflammatory response through the measurement of tumor necrosis factor-alpha (TNF-alpha). METHODS:Sixty rats were distributed into two groups: control and allopurinol and each group was divided into three subgroups, ischemia for two hours, ischemia for three hours and ischemia simulation. Allopurinol group rats received 100mg/kg dose of allopurinol, whereas control group rats received an equivalent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…TNF-a (tumor necrosis factor-a) is an inflammatory marker secreted by macrophages, monocytes, neutrophils, T-cells, NK-cells following their stimulation by bacterial lipopolysaccharides (Gomes et al, 2016). By performing pairwise comparison among the six tested groups, The TNF-a level showed significant difference among the six tested groups (p50.05).…”
Section: Resultsmentioning
confidence: 99%
“…TNF-a (tumor necrosis factor-a) is an inflammatory marker secreted by macrophages, monocytes, neutrophils, T-cells, NK-cells following their stimulation by bacterial lipopolysaccharides (Gomes et al, 2016). By performing pairwise comparison among the six tested groups, The TNF-a level showed significant difference among the six tested groups (p50.05).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there are also studies in which its oral administration prior to ischemia instauration does demonstrate an antioxidant effect, as evidenced by a reduction in HID and a decrease in the production of oxidative stress markers such as malondialdehyde (MDA) [33]. Other studies performed in a renal IRI mode have shown the beneficial effect of XO inhibition [34][35][36][37][38]. After prophylactic administration of allopurinol, a decrease of up to 75% in the damage was noticed, both biochemical and anatomopathological.…”
Section: Discussionmentioning
confidence: 99%
“…Gomes et al 18 demonstrates I/R-induced inflammation reduction, when comparing the efficiency of allopurinol in reducing serial concentration of tumor necrosis factors, of the I/R group, with groups submitted to I/R and treated with allopurinol. Allopurinol also displayed significant advantages in reducing injury by reperfusion in the kidneys of rats, which was demonstrated by Keel et al 19 , by the utilization of 8-isoprostane as oxidative stress marker in the evaluation of injury by I/R; Zhou et al 20 evidenced improvement in kidney function and histology.…”
mentioning
confidence: 99%